Religion, Attitude, and Entrepreneurship Intention in Indonesia - Sulung, Liyu Adhi Kasari; Putri, Niken Iwani Surya; Robbani, Muhammad Miqdad; Ririh, Kirana Rukmayuninda (UI Scholars Hub, 2020)
Research Aims: The present research investigates the relationships among behavioural belief, attitude toward entrepreneurship, religiosity, and entrepreneurial intention in Indonesia. Design/methodology/approach: We use a structural equation model supported by LISREL 8.80 to analyse a sample of 146 owners of micro and small enterprises. Research Findings: We found new results to add to the entrepreneurship literature regarding the relationship between religiosity and entrepreneurship. Although religiosity has been mostly discussed in previous research as a moderator, this study found that religiosity also has a strong direct relationship to entrepreneurial intention. Further, most of the independent variables also show a significant influence on entrepreneurial intention. Theoretical Contribution/Originality: Based on our result, this paper found that religiosity has a strong direct relationship to entrepreneurial intention. Our paper is also the first to aggregate behavioral beliefs through multiple religious points of view regarding entrepreneurial intention. Managerial Implication in the South East Asian context: The result can be applied to enhance entrepreneurship in South East Asian countries Research limitation & implications: The result has implications for entrepreneurship education, business practitioners, and policy makers to strengthen entrepreneurial intention. Furthermore, since affective attitude and instrumental attitude involve a reciprocal process over a long period, this study recommends that future research should apply longitudinal study